The Influence of Teachers' Social Competence and Personality Competence on the Emotional Intelligence of Children Aged 5-6 Years in Baubau City - Sitti Mutmainna Zakir; Muthmainah Muthmainah (Dinasti Publisher, 2025)
Low emotional intelligence in children will impact their behavior and actions. Armed with the competencies they possess, teachers play a major role in shaping children into academically and emotionally intelligent individuals. This study aims to examine the influence of social competence and teacher personality competence on the emotional intelligence of children aged 5–6 years, both individually and collectively. Using a quantitative ex post facto approach, the study involved 98 kindergarten group B teachers in Baubau City, selected through probability cluster sampling. Data were collected via questionnaires and analyzed using multiple linear regression, including F-tests, t-tests, and determination coefficient tests. The results of the study show that: (1) there is a positive influence of teachers' social competence on the emotional intelligence of children aged 5-6 years with a significance value of 0.001 < 0.05 and a contribution of 30,6%; (2) there is a positive influence of teachers' personality competence on the emotional intelligence of children aged 5-6 years with a significance value (2-tailed) 0.001 < 0.05 and a contribution of 30,7%; (3) there is a positive influence of social competence and teacher personality competence together on the emotional intelligence of children aged 5–6 years with a significance value (2-tailed) 0.000 < 0.05 and a contribution of 38%.